A rare case of aggressive angiomyxoma of vulva since childhood - Burute, Shankar B.; Jahnavi, T. Swetha; Ratwani, Karuna; Dharwadkar, Arpana A.; Kulkarni, Jayashree P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Aggressive angiomyxoma is a locally invasive benign mesenchymal tumour usually occurring in women of reproductive age and is rare in children. It carries a high risk of recurrence and hence needs to be differentiated from other masses. The diagnosis is difficult clinically and is almost always histological. Here is a rare case of aggressive angiomyxoma of vulva in a 15 year old female presented with presented with mass in vulva on left side since birth and increased to the present size since 3 years. The swelling was painless, no local rise of temperature, no visible veins. Attained menarche 2 years ago and cycles are regular with normal flow.